Echocardiographic assessment at rest and during stress in patients with intermittent claudication. (4th May 2019) - Nordanstig, Joakim; Bech-Hanssen, Odd; Skoog, Per; Jivegård, Lennart
Abstract: Objective . Skeletal muscle perfusion during walking relies on complex interactions between cardiac activity and vascular control mechanisms, why cardiac dysfunction may contribute to intermittent claudication (IC) symptoms. The study aims were to describe cardiac function at rest and during stress in consecutive IC patients, to explore the relations between cardiac function parameters and treadmill performance, and to test the hypothesis that clinically silent myocardial ischemia during stress may contribute to IC limb symptomatology. Design . Patients with mild to severe IC ( n = 111, mean age 67 y, 52% females, mean treadmill distance 195 m) underwent standard echocardiography, dobutamine stress echocardiography (SE) and treadmill testing. The patient cohort was separated in two groups based on treadmill performance (HIGH and LOW performance). Results . Ten patients (9%) had regional wall motion abnormalities of which three had left ventricular ejection fraction <50% at standard echocardiography. A majority had lower than expected systolic- and diastolic ventricular volumes. LOW performers had smaller diastolic left ventricular volumes and lower global peak systolic velocity during dobutamine stress. No patient demonstrated significant cardiac dysfunction during dobutamine provocation that was not also evident at standard echocardiography. Conclusions . Most IC patients were without signs of ischemic heart disease or cardiac failure. The majority had small left ventricular volumes. The hypothesis that clinically silent myocardial ischemia impairing left ventricular function during stress may contribute to IC limb symptomatology was not supported. Trial registration: ClinicalTrials.gov identifier: NCT01219842.